PENGARUH PERENCANAAN TENAGAKERJA, LINGKUNGAN KERJA TERHADAP PENINGKATAN KUALITAS PRODUK LAYANAN PERBANKAN SYARIAH - Eriswanto, Elan (JURNAL PENDIDIKAN AKUNTANSI & KEUANGAN, 2016)
The goals of research is to determine the effect employee planning anad working of environment the quality product services syariah banking at Sukabumi. This study using variables employee planning, working environment and the quality product service.This research using associative method with a quantitative approach. The  intrumens questionnaires distributed  156 respondents. Sampling method used purposive by  percentage, the data analysis method  regression test, test f and the coefficient of determination.The results  this study shows  that employee planning has minimum influence to the quality product services and working environment has effect on the  quality product services. Based on the results of research show that the test f employee planning and working environment effect on the  quality product services. Key words : Employee planning, working environment and quality product services